2022
DOI: 10.48550/arxiv.2210.08917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mars: Semantic-aware Contrastive Learning for End-to-End Task-Oriented Dialog

Abstract: Traditional end-to-end task-oriented dialog systems first convert dialog context into dialog state and action state, before generating the system response. In this paper, we first empirically investigate the relationship between dialog/action state and generated system response. The empirical exploration shows that the system response performance is significantly affected by the quality of dialog state and action state. Based on these findings, we argue that enhancing the relationship modeling between dialog c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…We observe that in most cases, error originates from incorrectly generated system action and dialog state. This hints at a direction for further improvement in lines of making dialog state and system action generation more robust (Sun et al, 2022b). 12354…”
Section: O Krls Error Examplesmentioning
confidence: 98%
See 1 more Smart Citation
“…We observe that in most cases, error originates from incorrectly generated system action and dialog state. This hints at a direction for further improvement in lines of making dialog state and system action generation more robust (Sun et al, 2022b). 12354…”
Section: O Krls Error Examplesmentioning
confidence: 98%
“…We present this result in Table 7, and found that +DST improved the overall score by nearly 4 points, and +Both further improved the overall score by 14.5 points, almost reaching the performance of the training dataset 4 . This shows that much error remains in the DST and system act generation process, so the overall performance can further increase if techniques to separately improve DST and system act generation (e.g., Sun et al (2022b)) can be combined with KRLS. We leave this for future work.…”
Section: Error Analysismentioning
confidence: 99%
“…Building task-oriented dialog (TOD) systems has been a long-standing challenge in artificial intelligence. The prevailing approach for creating task bots (Hosseini-Asl et al, 2020;Peng et al, 2021a;Sun et al, 2022) is to fine-tune pre-trained language models (PLMs), such as T5 (Raffel et al, 2020) and GPT-2 (Radford et al, 2019). Despite their great success, developing and maintaining such task bots generally requires adequate annotated data and extensive fine-tuning/re-training.…”
Section: Introductionmentioning
confidence: 99%
“…We evaluate both end-to-end and policy optimization settings. This includes UBAR (Nekvinda and Dusek, 2021), PPTOD (Su et 2022), RSTOD (Cholakov and Kolev, 2022), BORT (Sun et al, 2022a), MTTOD (Lee, 2021), HDNO (Wang et al, 2020a), GALAXY , MarCO (Wang et al, 2020b), Mars (Sun et al, 2022b), and KRLS . To obtain database search results in the end-to-end setting, we use MTTOD's dialogue state tracker, which is trained jointly during fine-tuning.…”
Section: Experiments Setupmentioning
confidence: 99%
“…Response generation is an important task in taskoriented dialogue systems. There have been many previous approaches (Hosseini-Asl et al, 2020;Gu et al, 2021;Su et al, 2022;Sun et al, 2022b;Wu et al, 2023) proposed to improve the task-oriented dialogue systems. One direction is the use of dialogue act annotations to improve the quality of responses in task-oriented dialogue systems.…”
Section: Introductionmentioning
confidence: 99%